Willingness-To-Pay versus Administrative Hurdles: Understanding Barriers to Social Insurance Enrollment in Thailand - Olken, Benjamin A.; Hanna, Rema; Poonpolkul, Phitawat; Wasi, Nada (The Review of Economics and Statistics, 2026)
Many social insurance programs have low take-up, but it is unclear whether this is due to administrative barriers, information, or low insurance valuations. We study a Thai policy that offered large incentives for informal workers in selected provinces to enroll. The incentives increased insurance coverage by 67 percentage points- from 6 percent of informal workers to 73 percent- within two months. However, 12 months later, only 13 percent remained insured. Using choices among insurance tiers to back out revealed valuations, we find that low social insurance enrollment may be due to low ex-ante valuations of insurance, rather than administrative barriers.